2014
DOI: 10.4314/ajtcam.v11i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of <i>Ficus Thonningii</i> Extracts On The Gastrointestinal Tract And Clinical Biochemistry Of Suckling Rats

Abstract: Background: Ficus thonningii is commonly used in traditional medicine across the African continent. We investigated the effects of crude Ficus thonningii extracts on growth, morphology and morphometry of the abdominal viscera and clinical biochemistry of neonatal rats. Materials and Methods: Forty, 6-day old Sprague Dawley rat pups were orally gavaged once daily with either low (50 mg.kg -1 b.w) or high (500 mg.kg -1 b.w) doses of aqueous or methanolic F. thonningii leaf extracts while the control received dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Oral administration of an aqueous calyx extract of Hibiscus sabdariffa to suckling rats for 9 days, resulted in early maturation of the small intestine and the cecum, as demonstrated by significantly increased organ weights relative to the control group (Ibrahim et al, 2017). Dangarembizi et al (2014) demonstrated a dose-dependent trophic effect on cecal mucosal layers of Sprague Dawley pups following the oral administration of a methanolic extract of Ficus thonningii for 7 days, starting from postnatal day 6. The findings were attributed to phytochemicals that can stimulate the release of regulatory peptides which then favor the proliferation of parietal cells, thus accelerating the growth of the gut mucosa (Jain and Samuelson, 2006).…”
Section: Impact Of Medicinal Plants and Phytochemicals On The Development And Maturation Of The Gastrointestinal Tractmentioning
confidence: 95%
“…Oral administration of an aqueous calyx extract of Hibiscus sabdariffa to suckling rats for 9 days, resulted in early maturation of the small intestine and the cecum, as demonstrated by significantly increased organ weights relative to the control group (Ibrahim et al, 2017). Dangarembizi et al (2014) demonstrated a dose-dependent trophic effect on cecal mucosal layers of Sprague Dawley pups following the oral administration of a methanolic extract of Ficus thonningii for 7 days, starting from postnatal day 6. The findings were attributed to phytochemicals that can stimulate the release of regulatory peptides which then favor the proliferation of parietal cells, thus accelerating the growth of the gut mucosa (Jain and Samuelson, 2006).…”
Section: Impact Of Medicinal Plants and Phytochemicals On The Development And Maturation Of The Gastrointestinal Tractmentioning
confidence: 95%
“…The extracted solution was then filtered through Whatman 1 filter paper. The filtrate was concentrated using a rotor evaporator (Labocon (Pty) Ltd, Krugersdorp, South Africa) and dried in an oven (Salvis ® ; Salvis Lab, Schweiz, Switzerland) at 40°C 39 . The dry extracts powder was collected and stored in dark, tightly sealed glass vials at 4°C for future use 34 …”
Section: Methodsmentioning
confidence: 99%
“…The filtrate was concentrated using a rotor evaporator (Labocon (Pty) Ltd, Krugersdorp, South Africa) and dried in an oven (Salvis ® ; Salvis Lab, Schweiz, Switzerland) at 40°C. 39 The dry extracts powder was collected and stored in dark, tightly sealed glass vials at 4°C for future use. 34,40 Study design A total of 85 4-day-old Sprague Dawley pups from nine dams that were sourced from the Central Animal Services, University of the Witwatersrand, were used in this study which was conducted in three stages.…”
Section: Plant Source Identification and Extractionmentioning
confidence: 99%
“…The filtrate was concentrated using a rotor evaporator (Labocon (Pty), Krugersdorp, South Africa). The extracts were then dried in an oven (Salvis ® , Salvis Lab, Schweiz, Switzerland) at 40 °C (Dangarembizi et al., ) and the residual powder extracts were collected and stored in dark, tightly sealed glass vials at 4 °C for future use (Ali et al., ; Lin et al., ). The yield from the aqueous extraction was 22%.…”
Section: Methodsmentioning
confidence: 99%